New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg? - Wood, Timothy S.; Okamura, Beth (Zootaxa, 2017)
This paper reports the occurrence of 11 species of freshwater bryozoans collected from the States of Pará and São Paulo, Brazil, including two new genera and four new species. Two new families are erected, Tapajosellidae n. fam. in the Class Phylactolaemata, and Natanellidae n. fam. in the Class Gymnolaemata, Order Ctenostomata. One new genus, Tapajosella n. gen., accommodates the new phylactolaemate genus and species, Tapajosella elongata n. sp. The other new genus, Natanella n. gen., includes the former ctenostome, Hislopia natans, now Natanella natans n. comb. Other new species are the phylactolaemates, Plumatella pirassununga n. sp., Plumatella jariensis n. sp., and Fredericella tenax n. sp. Additional species include the ctenostome Hislopia corderoi Mané-Garzón, 1960, and the phylactolamates Plumatella osburni (Rogick & Brown, 1942), Plumatella siolii Wiebach, 1970, Plumatella casmiana Oka, 1907, Plumatella marcusi Wiebach, 1970, and possibly Plumatella philippinensis Kraepelin, 1887. The notable expansion in diversity of freshwater bryozoans from Brazil revealed by material amassed during brief and spatially-limited collection is suggestive of considerable undiscovered diversity in this poorly studied region of the world.